Instruction Matters: Pedagogical Approaches to Increase Engagement in a Juvenile Detention Center. Issue 1 (14th December 2020) - Pytash, Kristine E.; Kosko, Karl W.
Abstract: Researchers have documented that high engagement in learning is linked to high academic achievement, and that low engagement is linked to low academic achievement, student alienation, and withdrawing from school. While research provides insights into student engagement and instructional practices, this research is typically conducted in traditional schools. The purpose of this study was to investigate students' engagement during an interdisciplinary instructional unit to better understand the instructional approaches that influenced student engagement in juvenile detention centers. 602 observation intervals and qualitative data demonstrated that students were most engaged when instruction included hands-on activities, multimedia use, literacy practices, and teacher-led discussions. This study provides implications for instructional design and approaches in juvenile detention centers.